Affect regulation in the context of sexual and gender minority stress: A scoping review protocol - Daphne Y. Liu; Benjamin A. Swerdlow; Shao Yuan Chong; Nadia Kako; Alex Rubin; Nicholas S. Perry (PLoS ONE, 2026)
Objective To provide a broad, comprehensive picture of affect regulation in the context of sexual and gender minority stress, this scoping review aims to identify and synthesize methods, methodologies, and available evidence pertinent to emotion regulation and coping in the context of minority stress among sexual and gender minority (SGM) people. Introduction SGM people face disproportionately high rates of mental health problems due to experiences of minority stress and lack of social safety. Theories and growing evidence suggest that affect regulation plays a critical role in SGM people’s well-being in the face of minority stress. Researchers have largely studied emotion regulation, coping, and minority stress in distinct literatures; as such, there is a critical need to synthesize evidence across these bodies of research. Inclusion criteria We will review empirical studies that (1) included SGM people, (2) measured at least one affect regulation construct, and (3) studied affect regulation in the context of sexual or gender minority stress. Methods Published and unpublished (i.e., grey literature) empirical studies written in English (no restrictions on publication date) will be searched using the following databases: PsycINFO (via EBSCO), Web of Science Core Collection (via Clarivate), PubMed (via National Library of Medicine), Gender Studies Database (via EBSCO), Sociological Abstracts (via ProQuest), and SocIndex with Full Text (via EBSCO). Grey literature will be identified through searching on additional repositories and databases and emailing listservs of relevant organizations. Potentially relevant papers will first be screened based on title and abstract, followed by full-text screening, against inclusion criteria by two independent reviewers. Data on study characteristics and findings relevant to the review will be extracted by two independent reviewers. Descriptive data relevant to each research question will be presented in tabular format, followed by a narrative summary of main findings, research gaps, and areas for future research.